If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 11y + -1 = 6y + 48 + -4y Reorder the terms: 4 + -1 + 11y = 6y + 48 + -4y Combine like terms: 4 + -1 = 3 3 + 11y = 6y + 48 + -4y Reorder the terms: 3 + 11y = 48 + 6y + -4y Combine like terms: 6y + -4y = 2y 3 + 11y = 48 + 2y Solving 3 + 11y = 48 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 3 + 11y + -2y = 48 + 2y + -2y Combine like terms: 11y + -2y = 9y 3 + 9y = 48 + 2y + -2y Combine like terms: 2y + -2y = 0 3 + 9y = 48 + 0 3 + 9y = 48 Add '-3' to each side of the equation. 3 + -3 + 9y = 48 + -3 Combine like terms: 3 + -3 = 0 0 + 9y = 48 + -3 9y = 48 + -3 Combine like terms: 48 + -3 = 45 9y = 45 Divide each side by '9'. y = 5 Simplifying y = 5
| 2x+33=4x+11 | | 8x+7=2x+31 | | 10x-7=113 | | 10-7=133 | | 6x+7=37 | | 5r-11=21+4(1-r) | | 12x-19=133 | | -4-6n=14-8n | | 6x+8=-88-10x | | 6x+8=-88-10x | | 135-2x=6x+23 | | 90-5n=9n+20 | | 5n+13=103-4n | | -2(2b+3)+(5b-3)=0 | | 5.2q-5.7-5.9q=-1.7q-4.5 | | 2x+7=57-3x | | 3(2x+11)=6x-33 | | 8+11n=78+n | | b=hr | | -4y+4=-5y+6 | | 4n-4=12n-76 | | 5n+20=15n+80 | | -(6y+4)-(-5y-8)=-2 | | 5n+20=15n+20 | | 10n-16=6n+4 | | X-2(3x-2)=-6 | | 2n+65=7n+10 | | 7x+5=16x | | 8(3x-9)=2(12x+3) | | 9n+5=4n+20 | | 7n-14=42 | | -3x+1=10 |